Jejak Komunitas Muslim di Burma: Fakta Sejarah yang Terabaikan - Ridwan Bustamam (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2013)
This paper is aimed at revealing the sensitive issues of early islamization of Burma (Mynmar) which are still debated by many historian. Besides reviewing the conflicting opinions, the paper also proposes a perspective that make it more reasonable based on the strong historical facts, especially from local sources of Burma. According to Muslim historian, Islam reached Burma, particularly Arakanese territory in the first hegira (in the seventh or the eighth century AD). Then, Islam became a popular religion in the nineth century, and became a religious power in the thirteenth century. The problem would be different opinion on the early Islamic community called Rohingya, the Muslim empire in existence also known as Burma Mrauk-U. Keywords: Burma, Arakan, Mrauk-U, Rohingya.